Long-Term Clinical Outcome after Treatment for High-Grade Cervical Lesions: A Retrospective Monoinstitutional Cohort Study. (9th June 2015) - Del Mistro, Annarosa; Matteucci, Mario; Insacco, Egle Alba; Onnis, GianLibero; Da Re, Filippo; Baboci, Lorena; Zorzi, Manuel; Minucci, Daria
Abstract : Background . The aim of this retrospective observational study of women treated for cervical intraepithelial neoplasia grade 2 or worse (CIN2+) was to assess the long-term risk of residual/recurrent high-grade CIN. Materials and Methods . We evaluated 760 women treated by loop electrosurgical excision procedure (684) or conization (76) between 2000 and 2009, and followed up to June 30, 2014 (median follow-up 6.7 years, range 4–14). Visits every 6 months for the first year after treatment and yearly for up to the following 10 years included cytology, colposcopy when indicated, and HPV testing (search and typing). Results . CIN2+ or vaginal intraepithelial neoplasia grade 2 or worse (VAIN2+) was detected in 67 cases (8.8%), 39 at first follow-up and 28 after one/more negative visits. The risk of CIN2+ was higher in case of positive margins (odds ratio (OR) 8.04, 95% CI 4.31–15.0), type 3 transformation zone (OR for CIN3 27.7, 95% CI 2.07–36.9), CIN3+ excision (OR 6.02, 95% CI 1.73–20.9), and positive high-risk HPV test at first follow-up (OR for HPV16: 20.6, 95% CI 6.8–62.6; OR for other hrHPV types: 18.3, 95% CI 5.9–57.0). Conclusion . Residual/recurrent high-grade CIN occurred in <9% cases, and the risk was associated with transformation zone type, lesion grade, margins status, and hrHPV test result at 6–12 months of follow-up.